Gambaran Status Kebersihan Gigi dan Mulut pada Pengidap HIV/AIDS di Yayasan Batamang Plus Bitung - Kinontoa, Fitrisya C.; Mintjelungan, Christy N.; Tambunan, Elita (Universitas Sam Ratulangi, 2017)
Abstract: Human immunodeficiency virus/acquired immune deficiency syndrome (HIV/ AIDS) is an infectious disease that attacks the immune system, therefore, the individual becomes more susceptible to opportunistic infections. The lower the dental and oral hygiene status are, the more susceptible an individual to opportunistic infections in the oral cavity due to the presence of HIV/AIDS. This study was aimed to obtain the status of oral and dental hygiene in individuals with HIV/AIDS at the Batamang Plus Foundation in Bitung. This was a descriptive study with a cross-sectional design. Data were obtained by examination of oral and dental hygiene status using OHI-S index. There were 30 respondents obtained by using total sampling method. The results showed that the highest percentage of the oral and dental hygiene status of the respondents (68% of male respondent and 57% of female respondents) was at moderate category. The average OHI-S was 2,2, categorized as moderate. Conclusion: Most respondents in this study had moderate category of oral and dental hygiene status.Keywords: human immunodeficiency virus, dental and oral hygiene statusÂ Abstrak: Human immunodeficiency virus/acquired immune deficiency syndrome (HIV/AIDS) merupakan penyakit menular yang menyerang sistem kekebalan tubuh seseorang sehingga lebih mudah terserang infeksi oportunistik. Semakin rendah status kebersihan gigi dan mulut seorang pengidap HIV/AIDS akan lebih memudahkannya terserang infeksi oportunistik pada rongga mulut. Penelitian ini bertujuan untuk mengetahui status kebersihan gigi dan mulut pada pengidap HIV/AIDS di Yayasan Batamang Plus Bitung. Jenis penelitian ialah deskriptif dengan desain potong lintang. Data diperoleh dari hasil pemeriksaan status kebersihan gigi dan mulut menggunakan indeks OHI-S. Terdapat 30 responden yang diperoleh mengunakan metode purposive sampling. Hasil penelitian memperlihatkan bahwa persentase tertinggi dari status kebersihan gigi dan mulut responden berada pada kategori sedang yaitu 68% responden laki-laki dan 57% responden perempuan. Rerata OHI-S yang diperoleh ialah 2,2 yang tergolong kategori sedang. Simpulan: Sebagian besar responden memiliki status kebersihan gigi dan mulut kategori sedang.Kata kunci: pengidap HIV/AIDS, kebersihan gigi dan mulut